Hypotrichosis with Juvenile Macular Dystrophy in a Patient with Cadherin 3 (CDH3) Mutation - Rishi, Ekta; Goel, Sugandha; Bassi, Shikha; Rishi, Pukhraj (Nepalese Journal of Ophthalmology, 2022)
Introduction: Hypotrichosis with juvenile macular dystrophy (HJMD) is an autosomal recessive disease with progressive macular degeneration leading to blindness in the first three decades of life along with hypotrichosis. Case: We herein report a case of a five year old boy with hypotrichosis with juvenile macular dystrophy diagnosed with multi-modal imaging which was later confirmed by genetic testing by whole genome sequencing. Observations: Fundus examination of both eyes revealed symmetrical hypopigmentation in peripapillary retinal pigment epithelium (RPE) involving posterior pole and surrounded by a mottled hyperpigmented border. Fundus autofluorescence showed central hypo autofluorescence with surrounding hyper autofluorescence corresponding to RPE atrophy and a faint hypo autofluorescence at the junction of normal retina. SD-OCT showed segmental outer retinal and choriocapillaris atrophy temporal to fovea with interdigitation zone and ellipsoid zone loss and RPE irregularities with hyperreflective subretinal deposits at the fovea. Electroretinogram showed normal waves but a slight reduction of b wave amplitude in both eyes. He had sparse scalp-hair. Conclusion: Children with reduced vision not falling into a typical macular degeneration should be examined systemically and may just have sparse scalp hair and still have a genetic disease. A regular follow-up should be emphasized in view of progressive nature of the disease.